PELATIHAN PENULISAN KARYA ILMIAH DAN ANALISIS DATA BAGI GURU SD NO. 56 INPRES KAMPUNG BARU MAJENE - Hikmah Hikmah; Asrirawan; Musafira; Mega Afsari; Siti Tanri Cici (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2024)
This dedication improves teachers' understanding of making scientific papers and analyzing data so they are no longer constrained in writing scientific papers and become competent teachers. This service activity was motivated by the problems of teacher partners of SD No. 56 Inpres Kampung Baru, which included 1) teachers being reluctant to take care of promotions, 2) lack of teacher understanding in doing scientific work, and 3) lack of teacher understanding in analyzing data. The solution to this problem is training in writing scientific papers and data analysis for SD No. 56 Inpres Kampung Baru, Majene teachers, using presentation, discussion, demonstration, and practice methods. The stages of implementing this community service are 1) the preparation stage, communication with partners related to problems faced by teachers; 2) the implementation stage, by providing training in writing scientific papers and data analysis, and 3) the monitoring and evaluation stage. Training on the preparation of scientific papers and data analysis has been carried out well based on the evaluation results of 95,45% of participants experiencing an increase in scientific paper writing skills and 96,1% of participants experiencing an increase in data analysis skills.  ---  Pengabdian ini untuk meningkatkan pemahaman guru dalam membuat karya ilmiah dan menganalisis data sehingga tidak lagi terkendala dalam menulis karya ilmiah dan menjadi guru yang kompeten. Kegiatan pengabdian ini dilatarbelakangi oleh permasalahan mitra guru SD No. 56 Inpres Kampung Baru yang meliputi 1) guru enggan untuk mengurus kenaikan pangkat, 2) kurangnya pemahaman guru dalam membuat karya ilmiah, 3) kurangnya pemahaman guru dalam menganalisis data. Solusi atas permasalahan tersebut berupa pelatihan penulisanan karya ilmiah dan analisis data bagi guru SD No. 56 Inpres Kampung Baru, Majene dengan menggunakan metode presentasi, diskusi, demonstrasi, dan praktik. Adapun tahapan pelaksanaan pengabdian kepada masyarakat ini, yaitu: 1) tahap persiapan, komunikasi dengan mitra terkait permasalahan-permasalahan yang dihadapi oleh guru, 2) tahap pelaksanaan, dengan memberikan pelatihan penulisan karya ilmiah dan analisis data, serta 3) tahap monitoring dan evaluasi. Pelatihan penyusunan karya ilmiah dan analisis data telah terlaksana dengan baik berdasarkan hasil evaluasi 95,45% peserta mengalami peningkatan kemampuan penulisan karya ilmiah dan 96,1% peserta mengalami peningkatan kemampuan analisis data.